Transformasi Pendidikan Global: Dari Kesenjangan Ke Kesetaraan Antara Negara Berkembang dan Maju - Kurnia Sofiani, Ika; Fitri, Norlaili; Aulia Putri, Safira; Rohayati, Siti (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Education is a fundamental pillar in sustainable human and social development as well as a vital instrument for economic growth and political stability. However, in the era of globalization, the education gap between developed and developing countries remains a significant issue, widening disparities in access and quality. This study employs a qualitative descriptive approach using library research methods, analyzing various secondary sources such as academic journals, international policy reports, and educational statistics. The aim of this research is to examine the global education transformation from inequality towards equity between developed and developing countries, as well as to identify the obstacles and enablers of this transformation. The benefit of this study is to provide a comprehensive overview that can assist policymakers in designing more inclusive and equitable education strategies. The results indicate that developed countries have successfully established inclusive, digital, and 21st-century competency-oriented education systems, while developing countries continue to face significant challenges related to infrastructure, teacher quality, funding, and technological readiness. The COVID-19 pandemic has highlighted the digital divide, exacerbating educational access issues in developing nations. Education transformation requires not only technological advancement but also curriculum reform, enhancement of teacher professionalism, and equitable multilateral cooperation. In conclusion, global education transformation towards equity demands a multidimensional approach, political commitment, and stakeholder synergy to ensure education as a basic right that is accessible and of high quality for all humanity